Fossil cold-water corals (Scleractinia and Gorgonacea) from the Burdwood Reef, Argentina Republic - Isla, Federico Ignacio (2023)
The Burdwood Bank is a rocky platform emerging from the abyssal plain to depths of 50-100 m between the South Atlantic Ocean and the Drake Passage. Regarding its geological affinity, it has a composition similar to the Staten Island (Isla de los Estados), therefore aligned to the Andes-Darwin Cordillera. This bank is crossed from south to north by the Antarctic Bottom Water; very cold and rich in nutrients. Rocks dredged from the shallower portions at its western portion are composed of carbonatic blocks. The analyses indicated fossil specimens of Desmophyllum sp. (Or-der Scleractinia) and Gorgonacea palmatum (Order Gorgonacea), genera living today in the region. In this sense, sectors of this western portion should be considered as an ancient reef composed mostly of cold-water corals. The major implications are assigned to oceanographic and climatic issues. During the Upper-Pleistocene low-stand, the sunlight was more available at shallower depths and therefore corals were very frequent at wave-dominated areas. Sea-level variations have therefore strong influence on some cold-water coral growths in the sense that nutrient availability by currents can significantly changed between glacial and interglacial periods.